Feasibility Study On Supply Chain Management For MRO Industry In Malaysia - Mat Daud, Mohd Faiz (2019)
This thesis secks to study the best practices of supply chain management for acrospace industry in Malaysia. In order to do that there is the needs of doing the feasibility study to get the better understanding of the supply chain activitics, key principles, and practices characterizing the creation of excellent supply chain management within the industry. The aim of this proposal is to conduct a benchmarking of the best practices in supply chain management in the Maintenance, Repair and Overhaul (MRO) industry; which is one of a big part for acrospace industry; and how these practices impact the compeltitive positioning of the third party MRO company (without airlines) within the industry. The analysis involves a broad review of the industry current state and future directions of the MRO industry by tracing the key factors shaping its evolution and by identifying the major strategic forces that would influence its future. A three-pronged methodology was adopted. The focus will be to benchmark the best practice of supply chain management for MRO industry in Malaysia. First, a framework was developed to identify the role of major factors that have proven crucial to effective supply chain management within the company. Second, case study examples that the framework was applied 10 a set of running MRO companies by tracking the implementation and results of major supply chain management initiatives, Third, the supply chain design and management practices are analyzed from the perspective of their SCM performance in the company's business strategy. The study offers a benchmark of current best practices supply chain management initiatives for MRO industry in Malaysia and the future initiatives that can be applied within the industry by looking at the gap and opportunity based on study analysis result. The examined set of companies, although representative (i.c. the analyzed companies operate in industrics in which the environmental concern is particularly critical), is limited. However, the present study contributes to the knowledge on supply chain management practices inside MRO industry and captures variations in theory, paving the way for new study. The thesis provides an instrument to evaluate and compare the current MRO company approach in terms of supply chain management and highlights the main challenges that companies have to confront. The originality of the thesis lies in the adoption of a supply chain perspective to investigate the initiatives that been applied within the acrospace industry in Malaysia.